Lithuanian Consumer`s Willingness to Pay and Feed-in Prices for Renewable Electricity - Dalia Streimikiene; Asta Mikalauskiene (Amfiteatru Economic)
The paper aims to assess the willingness to pay (WTP) for renewable electricity of Lithuanian households and to compare WTP of Lithuanian consumers with support provided for renewable by Lithuanian government in terms of Feed-in prices. The paper reviews the situation of renewable electricity generation and consumption in Lithuania and presents the results of empirical study aiming at assessment of Lithuanian household’s willingness to pay for electricity produced from renewables. The results of study indicated that the WTP of Lithuanian households is significantly lower than subsides for renewable electricity provided in the form of Feed-in prices in Lithuania. Therefore feed-in prices need to be revising taking into account WTP of Lithuanian consumers